Adaptation to Social Complexity - M. S. Negrova (Vestnik MGIMO-Universiteta)
Modern Society as a Complex Dynamic System is Affected by Unforeseen Fluctuations. By Historical Standards, the Recent Introduction of the Nonlinear Approach into the Scientific World Picture put the Classical Understanding of Space and Time to the Obstruction. Consequently, there Appeared the Problem of Human Adaptation and his Worldview to the Asserting Complexity of the Society